Coal efficiency, carbon reduction, and future policy perspective in Pakistan’s economic growth: a decomposition and decoupling approach - Raza, Muhammad Yousaf; Lin, Boqiang (Frontiers in Energy Research, 2023)
Pakistan is moving toward large-scale use of coal. Coal will play a dominant role in Pakistan’s energy mix, reaching 30% by 2030. The purpose of this study is to analyze coal imports and indigenous reserves in relations to CO2 emissions. In particular, this study constructs the LMDI method to see factor’s impact, decoupling index for the economic relationship, and pollution from coal-fired power plants from 1986-2019. The empirical results show that (1) coal consumption and imports are interrelated, while coal production has had the lowest production level since 1986. (2) The energy intensity impact shows a medium role in declining coal utilization, followed by the coal share effect; however, the aggregated impact counts for 0.023% of the total coal use. (3) The economic and population activity effects progressively increase with coal consumption by 0.25% and 0.35% with annual average growth. (4) Only ‘3’ decoupling states seemed: expansive coupling, expansive negative and weak decoupling. Expansive negative decoupling occurred due to high energy share and energy intensity. Expansive coupling occurred only in 2001 due to fast growth in coal proportion and a sluggish fall in energy intensity, and weak decoupling showed a decoupling association between economic growth and coal utilization. (5) Using the various coal compositions, such as moisture, volatile matter, fixed carbon, ash, and Sulphur, be evaded by 1.82, 4.83, 5.16, 1.43, and 0.39Mt during the current time. Finally, environmental analysis recognized that implementing clean coal technologies significantly saves fuel and consequently reduces emissions. Further policies are provided below.